2007
DOI: 10.1016/j.str.2007.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an IgNAR-AMA1 Complex: Targeting a Conserved Hydrophobic Cleft Broadens Malarial Strain Recognition

Abstract: Apical membrane antigen 1 (AMA1) is essential for invasion of erythrocytes and hepatocytes by Plasmodium parasites and is a leading malarial vaccine candidate. Although conventional antibodies to AMA1 can prevent such invasion, extensive polymorphisms within surface-exposed loops may limit the ability of these AMA1-induced antibodies to protect against all parasite genotypes. Using an AMA1-specific IgNAR single-variable-domain antibody, we performed targeted mutagenesis and selection against AMA1 from three P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 55 publications
1
84
0
Order By: Relevance
“…Henderson et al . 69 suggested that recognition of a conserved hydrophobic cleft on Plasmodium AMA1 by a V NAR (12Y-2 and its affinity-matured variants) reflected a novel binding mode; although the epitope of a murine conventional antibody (1F9) substantially overlapped that of V NAR 12Y-2, 1F9 binding depended to a greater degree on polymorphic loop residues surrounding the hydrophobic trough. Likewise, Ditlev et al .…”
Section: Single-domain Antibodies Directed Against Folded Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Henderson et al . 69 suggested that recognition of a conserved hydrophobic cleft on Plasmodium AMA1 by a V NAR (12Y-2 and its affinity-matured variants) reflected a novel binding mode; although the epitope of a murine conventional antibody (1F9) substantially overlapped that of V NAR 12Y-2, 1F9 binding depended to a greater degree on polymorphic loop residues surrounding the hydrophobic trough. Likewise, Ditlev et al .…”
Section: Single-domain Antibodies Directed Against Folded Proteinsmentioning
confidence: 99%
“…Additional examples of binding to recessed epitopes on proteins (clefts, cavities, crevices or grooves) can be found for sdAbs against lactococcal siphophage, 97 Plasmodium falciparum MTIP, 98 epidermal growth factor receptor, 99 and respiratory syncytial virus fusion protein, 100 although in these cases it is less clear that these sites are inaccessible to conventional antibodies. While it is possible that V NAR s may share similar cleft-binding proclivities, such claims are based on very limited published data (three structures 7,12,69 ). Moreover, it should be noted that there are many examples (not covered in this review) of partial or complete overlap between the epitopes of sdAbs and conventional antibodies, and thus the degree to which sdAbs bind cryptic epitopes vs .…”
Section: Single-domain Antibodies Directed Against Folded Proteinsmentioning
confidence: 99%
“…For A␤-IgNAR-G1, note replacement of A␤ Ala42 with glycine, which modeling suggested was required to allow sufficient rotational freedom for realignment of the loop structure. A␤-IgNAR gene constructs were produced by splice-overlap PCR as previously described (Henderson et al, 2007) using IgNAR 12Y-2 DNA template and A␤ oligonucleotide primers (supplemental Table S1, available at www.jneurosci.org as supplemental material). DNA cassettes were cloned into Escherichia coli periplasmic expression vector pGC as described (Henderson et al, 2007).…”
Section: Construction Of A␤-ignar Chimerasmentioning
confidence: 99%
“…However, none of these antibodies has shown the ability to inhibit cell proliferation or induce apoptosis, possibly because of the difficulty of having a conventional antibody targeting the potentially cryptic functional epitope of GPC3. Because of their small size, domain antibodies are able to target cryptic epitopes on antigens (e.g., in the clefts of enzymes and receptors) (28)(29)(30).…”
mentioning
confidence: 99%